Rock-magnetic proxies of wind intensity and dust since 51,200 cal BP from lacustrine sediments of Laguna Potrok Aike, southeastern Patagonia - Lisé Pronovost, Agathe; St Onge, Guillaume; Gogorza, Claudia Susana; Haberzettl, Torsten; Jouve, Guillaume; Francus, Pierre; Olhendorf, Christian; Gebhardt, Catalina; Zolitschka, Bernd; The Pasado Science Team (Earth and Planetary Science Letters)
The sedimentary archive from Laguna Potrok Aike is the only continuous record reaching back to the last Glacial period in continental southeastern Patagonia. Located in the path of the Southern Hemisphere westerly winds and in the source region of dust deposited in Antarctica during Glacial periods, southern Patagonia is a vantage point to reconstruct past changes in aeolian activity. Here we use high-resolution rock-magnetic and physical grain size data from site 2 of the International Continental scientific Drilling Program (ICDP) Potrok Aike maar lake Sediment Archive Drilling prOject (PASADO) in order to develop magnetic proxies of dust and wind intensity at 52°S since 51,200 cal BP. Rock-magnetic analysis indicatesthe magnetic mineral assemblage is dominated by detrital magnetite. Based on the estimated flux of magnetite to the lake and comparison with distal dust records from the Southern Ocean and Antarctica, kLFis interpreted as a dust indicator in the dust source of southern Patagonia at the millennial time scale, when ferrimagnetic grain size and coercivity influence areminimal. Comparison to physical grain-size data indicates that the median destructive field of isothermal remanent magnetization(MDFIRM) mostly reflects medium to coarse magnetite bearing silts typically transported by winds for short-term suspension. Comparison with wind-intensity proxies from the Southern Hemisphere during the last Glacial period and with regional records from Patagonia since the last deglaciation including marine, lacustrine and peat bog sediments as well as speleothems reveals similar variability with MDFIRMup to the centennial time scale. MDFIRMis interpreted as a wind-intensity proxy independent of moisture changes for southeastern Patagonia, with stronger winds capable of transporting coarser magnetite bearing silts to the lake. Fil: Lisé Pronovost, Agathe. Université du Québec à Rimouski. Canada Research Chair in Marine Geology. Institut des sciences de la mer de Rimouski; Canadá. GEOTOP Research Center; ...